Sikap bahasa mahasiswa laki-laki dan perempuan di Jurusan Sastra Jerman Universitas Negeri Malang - Sobara, Iwa; Ardiyani, Dewi Kartika (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This study aimed to descriptively analyze language attitudes among male and female students as reflected in three characteristics: (1) language loyalty, (2) language pride, and (3) awareness of language norms. The research employed a descriptive qualitative design and was conducted at the German Department, Faculty of Letters, State University of Malang. The data sources consisted of ten students, comprising five male and five female students. Data were collected through classroom observations and questionnaires. Based on the findings, it can be concluded that the language attitudes of both male and female students were categorized as good.